ANALISIS TINGKAT PENGETAHUAN MASYARAKAT TERHADAP PEMANFAATAN PELAYANAN KESEHATAN DI PUSKESMAS PANONGAN KABUPATEN TANGERANG TAHUN 2023 - Salsabila Shafa (2023)
The level of utilization of health care facilities by the community reflects the quality of services provided and as well as indicating the level of patient trust in the provision of health services. The number of outpatient visits at the Puskesmas Panongan has decreased significantly from 2020 to 2022. This study aims to analyze the relationship between the level of community knowledge and the utilization of health services at the Panongan Health Center. The study used a cross-sectional design with simple random sampling technique and was conducted on 111 respondents. The results of the chi square test showed that there was a relationship between the level of knowledge (p value = 0.000) with the utilization of health services at the Puskesmas. The conclusion obtained is that the level of knowledge is related to the utilization of health services at the Puskesmas. It is expected that the community can make maximum use of health services at the Puskesmas and seek more information through health workers at the Puskesmas or independently through trusted sources related to available health services.